The Use of Educational Videos to Enhance Self-Awareness in Hypertension Patients - Yunita, Rizka; Yaqin, Moh. Husyn Ainul (Journal of Nursing Science Update (JNSU), 2024)
Hypertension is a significant cause of morbidity and mortality worldwide. Patients who struggle to manage their blood pressure risk severe complications such as stroke, heart failure, and kidney disease. A critical factor in their inability to control blood pressure is a lack of self-awareness about their condition. This study aimed to evaluate the impact of educational videos about hypertension on the self-awareness of patients diagnosed with this condition. This research employed a pre-experimental one-group pre-post-test design, with a total study population of 48 individuals with hypertension. Utilizing a purposive sampling method, the sample for this investigation consisted of 43 participants. The primary instrument for data collection was a self-awareness questionnaire, and the Wilcoxon test was utilized for data analysis. The findings revealed that 27 participants (63%) exhibited a low level of self-awareness prior to the implementation of the educational videos. By lowering the intervention, the number of participants achieving a high level of self-awareness similarly increased to 27 (63%). The results show a significant effect of the hypertension educational videos on the patients' self-awareness, with a p-value of 0.001. The educational videos incorporated images, symbols, and animations, accompanied by audio elements, facilitating effective communication of information about hypertension. In conclusion, educational videos assist individuals in comprehending and applying the knowledge presented, ultimately enhancing their awareness of the importance of hypertension management.